73. Geographical Disparities in Clinical Outcomes of Severe COVID-19 Patients Treated with Remdesivir - Diaz, George (Open Forum Infect Dis, 2020)
BACKGROUND: Remdesivir (RDV), a RNA polymerase inhibitor with potent in vitro activity against SARS-CoV-2, is the only treatment with demonstrated efficacy in shortening the duration of COVID-19. Here we report regional differences in clinical outcomes of severe COVID-19 patients treated with RDV, as part of an open-label, randomized phase-3 trial establishing RDV treatment duration. METHODS: Hospitalized patients with oxygen saturation ≤94%, a positive SARS-CoV-2 PCR in the past 4 days and radiographic evidence of pneumonia were randomized 1:1 to receive 5d or 10d of intravenous RDV. We compared d14 clinical outcomes of patients from different geographical areas, as measured by mortality rates, change in clinical status from baseline (BL) on a 7-point ordinal scale and change in O2 requirements from BL. Based on previous analyses in compassionate use data showing region as an important predictor of outcome, Italy was examined separately from other regions. RESULTS: 397 patients were treated with RDV, of which 229 (58%) were in the US, 77 (19%) Italy, 61 (15% in Spain), 12 (3%) Republic of Korea, 9 (2%) Singapore, 4 (1%) Germany, 4 (1%) Hong Kong and 1 (< 1%) Taiwan. BL clinical status was worse in Italy compared to other regions (72% vs 17% requiring high-flow oxygen delivery or higher), and Italian patients were more likely to be male than patients from other regions (69% vs 63%). Overall results showed 5d RDV was as effective as 10d. Mortality at d14 was higher in Italy (18%) compared to all other countries except Italy (7%). Similarly, clinical improvement at d14, measured as ≥2-point increase in the ordinal scale, was lower in Italian patients (39%) compared to all other countries combined (64%). (Fig.1). Figure 1. Change from Baseline in Clinical Status (measured on a 7-point Ordinal Scale) at d14. [Image: see text] CONCLUSION: Overall, our results demonstrate significant geographical differences in the clinical course of severe COVID-19 patients treated with RDV. We observed worse outcomes, such as increased mortality and lower rate of clinical improvement, in patients from Italy compared to other regions. DISCLOSURES: George Diaz, MD, NO DISCLOSURE DATA Jose Ramon Arribas, MD, Alexa (Advisor or Review Panel member, Speaker’s Bureau, Other Financial or Material Support, Personal fees)Gilead Sciences Inc. (Scientific Research Study Investigator, Advisor or Review Panel member, Speaker’s Bureau, Other Financial or Material Support, Personal fees)Janssen (Advisor or Review Panel member, Speaker’s Bureau, Other Financial or Material Support, Personal fees)Merck (Advisor or Review Panel member, Speaker’s Bureau, Other Financial or Material Support, Personal fees)Viiv Healthcare (Advisor or Review Panel member, Speaker’s Bureau, Other Financial or Material Support, Personal fees) Jose Ramon Arribas, MD, NO DISCLOSURE DATA Philip A. Robinson, MD, NO DISCLOSURE DATA Anna Maria Cattelan, MD, NO DISCLOSURE DATA Karen T. Tashima, MD, Bristol-Myers Squibb (Research Grant or Support)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator)GlaxoSmithKline (Research Grant or Support)Merck (Research Grant or Support)Tibotec (Research Grant or Support)Viiv Healthcare (Research Grant or Support) Owen Tak-Yin Tsang, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Owen Tak-Yin Tsang, MD, NO DISCLOSURE DATA Yao-Shen Chen, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Yao-Shen Chen, MD, NO DISCLOSURE DATA Devi SenGupta, MD, Gilead Sciences Inc. (Employee, Shareholder) Elena Vendrame, MD, NO DISCLOSURE DATA Christiana Blair, MS, Gilead Sciences (Employee, Shareholder) Anand Chokkalingam, PhD, Gilead Sciences (Employee) Anu Osinusi, MD, Gilead Sciences (Employee) Diana M. Brainard, MD, Gilead Sciences (Employee) Bum Sik Chin, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Bum Sik Chin, MD, NO DISCLOSURE DATA Christoph Spinner, MD, AbbVie (Advisor or Review Panel member, Other Financial or Material Support, Travel)Bristol-Myers Squibb (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Travel)Janssen (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)MSD (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)Viiv Healthcare (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel) Gerard J. Criner, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)Regeneron (Scientific Research Study Investigator) Gerard J. Criner, MD, NO DISCLOSURE DATA Jose Muñoz, MD, NO DISCLOSURE DATA David Chien Boon Lye, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Chien Boon Lye, MD, NO DISCLOSURE DATA Robert L. Gottlieb, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)